El transporte internacional como factor trascendental en la logística en países de América Latina caso “Colombia” (2021)
In this document, the issue of international cargo transportation is addressed, due to the impact it has on the competitiveness of companies in Latin American countries, in this particular case the importance it has in Colombia is analyzed, identifying its importance in the logistics for the country's foreign trade, the level of development of the different modes of transport, together with the analysis of the improvement and investment of the transport infrastructure within the country.